The acceptance, usage and impact of social media among university students - Ika Destiana,; Ali Salman, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
The emergence of new media, especially in the field of information and communication technology (ICT) will always cause a reaction to the users. These reactions can be the adoption of the new media, or even the rejection. The developing of ICT has become more profitable in human daily lives (Sensuse and Prayoga 2010) and social media is one growing phenomenon of communication on the internet in today’s world. Therefore, this paper discusses the factors that influenced the adoption and use of social media among students and how their experience of using social media is impacting on their involvement in social and political participation. Base on the Technology Acceptance Model (TAM) by Davis (1989) which consists of two main factors viz. perceived ease of use and perceived usefullness, this article, in extending the model also adds other factors that have not been described in the TAM such as social influences.